New Discourses for a Necessary Transformation: Intersectionality, Emerging Narratives, and Inclusive Education in Spain - Calderón-Almendros, Ignacio; Rascón-Gómez, María Teresa; Mojtar Mendieta, Luz del Valle (My University, 2022)
The presentation will describe the project “Emerging Narratives on the Inclusive School from the Social Model of Disability: Resistance, resilience and social change”. The project aims to dismantle forms of oppression at the personal, relational, and structural levels through (a) life histories of people experiencing intersecting forms of oppression and (b) action-oriented narratives for the expansion of collective imaginations. In particular, the paper presents Sandra's life story (experiencing oppression at the intersections of disability, transgender, and drug addiction), the process of building a campaign for inclusive education generated by activist families, and the work of a very diverse group of students that generates proposals for other students to promote inclusion in their own schools.
Keywords: Educación Inclusiva; Interseccionalidad; Narrativas emergentes